Mass transfer characteristics of pipeline leak-before-break in a nuclear power station. (September 2018) - Yin, Songtao; Weng, Yu; Song, Zichen; Cheng, Bo; Gu, Hongfang; Wang, Haijun; Yao, Jianan
Highlights: The two-phase critical flow model is modified in this paper. An algorithm is compiled and calculated accurately. The effects of the inlet conditions on the nucleation inception point are analyzed. The mass transfer process in the narrow channel is explored. Abstract: This paper aims to develop a correlation for pressure undershoot and revises the hypotheses of nucleation inception in the two-phase critical flow model. The theories of rapid depressurization and isothermal bubble growth were used to construct a modified two-phase critical flow model for leak-before-break analysis. The modified model predictions exhibit strong similarities with the experimental values compared with the Moody and Henry–Fauske models, with prediction deviations of less than 8.9% in the inter-granular stress corrosion crack. The effects of the inlet conditions on the nucleation inception point, as well as the distribution characteristics of the mass quality and void fraction along the channel, were investigated to explore the mass transfer process.